Dietary Patterns and Oxidative Stress in a Population of Women with Breast Cancer in the North-Western Regions of Algeria (Saida and El-Bayadh) - Halla, Noureddine; Boucherit, Kebir; Hachem, Kadda; Asmouni, Amouria; Derrab, Hanane; Boucherit-Otmani, Zahia (Journal of Drug Delivery and Therapeutics, 2020)
Objective: The aim of this work is the study of risk factors for breast cancer in a population of women in the north-western regions of Algeria (Saida and El-Bayadh)Methodology: A case-control study was carried out on 40 women including 20 cancerous women and 20 control women, in order to determine the dietary patterns and general characteristics of the population studied and to compare the hematological and biochemical parameters, and markers of oxidative/antioxidant status between control women and breast cancer women.Results: The results obtained show that there is no significant difference in the average age however the body mass index was significantly increased in cancer women, revealing overweight (p